2020
DOI: 10.1038/s41598-020-66706-2
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-plasmonic nanostars for image-guided and NIR-triggered drug delivery

Abstract: Smart multifunctional nanoparticles with magnetic and plasmonic properties assembled on a single nanoplatform are promising for various biomedical applications. Owing to their expanding imaging and therapeutic capabilities in response to external stimuli, they have been explored for on-demand drug delivery, image-guided drug delivery, and simultaneous diagnostic and therapeutic (i.e. theranostic) applications. In this study, we engineered nanoparticles with unique morphology consisting of a superparamagnetic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 59 publications
0
37
0
Order By: Relevance
“…Among various nanoparticles, plasmonic NPs and magnetic NPs are widely used in biological applications, but each have certain drawbacks that can be complimented by the other type of the NPs [ 51 ]. For example, the weakness of magnetic NPs such as toxicity [ 52 , 53 ], aggregation [ 54 , 55 , 56 ], easy corrosion in water [ 52 ] makes it difficult to work well in biological environments [ 52 , 53 , 54 , 55 , 56 ], while Au NPs hardly detect small amounts (giving low signal) of molecules in the mixture by SERS technology [ 57 , 58 ].…”
Section: Bioapplication Of Mppsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among various nanoparticles, plasmonic NPs and magnetic NPs are widely used in biological applications, but each have certain drawbacks that can be complimented by the other type of the NPs [ 51 ]. For example, the weakness of magnetic NPs such as toxicity [ 52 , 53 ], aggregation [ 54 , 55 , 56 ], easy corrosion in water [ 52 ] makes it difficult to work well in biological environments [ 52 , 53 , 54 , 55 , 56 ], while Au NPs hardly detect small amounts (giving low signal) of molecules in the mixture by SERS technology [ 57 , 58 ].…”
Section: Bioapplication Of Mppsmentioning
confidence: 99%
“…Therefore, they can be used as both SERS substrates and traditional magnetic NPs. Also, the interplay between the magnetic core and the plasmonic shell in the hybrids exhibits a synergistic effect in thermotherapy and bioimaging [ 21 , 51 ]. Some studies have reported on Fe-Au core shell MPPs, where the Au shell reduces the overall magnetic property, but this property is strong enough for MPP to act as a magnetic NP [ 21 , 35 , 51 ].…”
Section: Bioapplication Of Mppsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the past decade, nanoplasmonics was employed for the production of photovoltaic devices [1][2][3][4][5][6], optical devices [7][8][9][10][11][12][13][14][15], and biosensors [16][17][18][19][20]. Additionally, nanoplasmonics enabled the enhancement of photocatalysis [21][22][23], the luminescence upconversion enhancement [24,25], and the optical tuning of luminescence and upconversion luminescence [26,27].…”
Section: Introductionmentioning
confidence: 99%